Interaction of Machining Parameters on MRR of Sintered NdFeB Processed by EDM-Milling - Xinyu Zhang; Xue Bai; Tingyi Yang; Li Li (Applied Sciences)
Sintered Neodymium–iron–boron (NdFeB) exhibits high hardness and brittleness, resulting in low electrical discharge machining (EDM) efficiency. The study on the interaction effect of parameters on the material removal rate (MRR) of sintered NdFeB processed by EDM-milling is carried out to improve machining efficiency. The interaction significance of parameters on the MRR is analysed based on the interaction curve of two parameters. Meanwhile, the variation of MRR caused by the change in △y(x), △y x, and the sum and product of △y(x) are obtained by calculation. The interaction significance of parameters on MRR is obtained by comparing the sum and product of △y(x), while the significance of each parameter on MRR is obtained by comparing △y(x) and △y x. The reasons for the variation of interaction significance are revealed by analysing the differences in crater diameters and discharge waveforms. It is concluded that different levels of interactions exist between the processing parameters. The interaction between pulse on time and pulse off time affects the MRR most significantly, and current affects the MRR most significantly among single factors. The interaction of parameters can affect processes such as dielectric breakdown, discharge channel expansion, discharge energy and its utilisation, dielectric deionisation, significantly affecting the MRR of sintered NdFeB processed by EDM-milling.